Disease persistence and serotype coexistence: An expected feature of human mobility - Vilches, T. N. [UNESP]; Esteva, L.; Ferreira, C. P. [UNESP] (My University, 2019)
We present a stochastic model that mimics dengue transmission when two serotypes of the virus are circulating in a human population connected by a Watts–Strogatz complex network that reflects social interactions (human mobility). The influence of the number of connections per vertex and the network topology on the epidemics is analyzed. The first relation displays a sigmoid curve, while the second one shows that the increase in the network disorder facilitates disease spreading and serotype coexistence. The disease transmission thresholds for three network topology (regular, small-world and random) were obtained. Numerical results show that when coexistence of serotypes is a feasible outcome, negative correlation between the temporal evolution of the two serotype is more likely to occur. This could explain serotype dominance in consecutive epidemics.
Keywords: Dengue virus; Epidemic threshold; Mean-field limit; Network topology